High chromosomal mobility of rDNA clusters in holocentric chromosomes of Triatominae, vectors of Chagas disease (Hemiptera‐Reduviidae). Issue 1 (3rd November 2021) - Pita, S.; Lorite, P.; Cuadrado, A.; Panzera, Y.; De Oliveira, J.; Alevi, K. C. C.; Rosa, J. A.; Freitas, S. P. C.; Gómez‐Palacio, A.; Solari, A.; Monroy, C.; Dorn, P. L.; et al.
Abstract: The subfamily Triatominae (Hemiptera‐Reduviidae) includes more than 150 blood‐sucking species, potential vectors of the protozoan Trypanosoma cruzi, causative agent of Chagas disease. A distinctive cytogenetic characteristic of this group is the presence of extremely stable chromosome numbers. Unexpectedly, the analyses of the chromosomal location of ribosomal gene clusters and other repetitive sequences place Triatominae as a significantly diverse hemipteran subfamily. Here, we advance the understanding of Triatominae chromosomal evolution through the analysis of the 45S rDNA cluster chromosomal location in 92 Triatominae species. We found the 45S rDNA clusters in one to four loci per haploid genome with different chromosomal patterns: On one or two autosomes, on one, two or three sex chromosomes, on the X chromosome plus one to three autosomes. The movement of 45S rDNA clusters is discussed in an evolutionary context. Our results illustrate that rDNA mobility has been relatively common in the past and in recent evolutionary history of the group. The high frequency of rDNA patterns involving autosomes and sex chromosomes among closely related species could affect genetic recombination and the viability of hybrid populations, which suggests that the mobility of rDNA clusters could be a driver of species diversification. Abstract : Triatomines present one to four 45S rDNA loci per haploid genome, with most species having one locus in autosomal location (51 in 92 species), similar as other hemipteran groups. Different location patterns are observed: On 1 or 2 autosomes, on 1, 2 and 3 sex chromosomes, and on 1 to 3 autosomes plus X chromosome. The high diversity of rDNA patterns among closely related species suggests that the mobility of rDNA clusters could be a driver of species diversification in triatomines.